HUBUNGAN POLA ASUH ORANG TUA DAN FUNGSI PERAWATAN KESEHATAN KELUARGA DENGAN PERILAKU SULIT MAKAN PADA ANAK USIA PRA SEKOLAH DI KELURAHAN RAMBUTAN - Bunga Salsabilla Rayhan (2020)
Pre-school children are children aged 3-6 years. During this time children experience changes in eating patterns such as difficulty in eating in the form of not wanting to eat, eating time ≥ 30 minutes, and choosing food. The contributing factors are parenting and family health care. The purpose of this study was to determine the relationship between parenting parents and family health care with eating disorders in pre-school age children in Kelurahan Rambutan. The study used a cross sectional approach, with a total sample of 48 families having pre-school age children. The results showed there was a relationship between parenting parents with difficult eating behavior in pre-school age children with p- value 0.002 and OR = 10,000, which means pre-school age children have good parenting can increase positively difficult eating behavior towards 10,000 times, and there is also a relationship between family health care with eating disorders in pre-school age children with p-values of 0,000 and OR = 25,000, which means parents who implement good family health care functions can increase the behavior of eating disorders towards positive pre-school age children by 25,000 times. The results of the study can be used as information to pay more attention to parenting and family health care in children.